2019
DOI: 10.1021/acsami.9b13170
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Au/TiO2 Catalyst Thermostability and Coking Resistance with Alkyl Phosphonic-Acid Self-Assembled Monolayers

Abstract: Metal oxide-supported Au catalysts, particularly those with small Au nanoparticles, catalyze a variety of reactions including low-temperature CO oxidation and selective hydrogenation of alkynes. However, the facile nature of Au particle growth at even moderate temperatures poses significant challenges to maintaining catalyst activity under reaction conditions. Here, we present a method to reduce the rate of sintering and coke formation in TiO2-supported Au catalysts via the deposition of alkyl-phosphonic acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 41 publications
0
43
0
Order By: Relevance
“…It has been reported that the gold catalysts can sometimes show hydrogenation activity when gold nanoparticles or atoms are supported on reducible oxides 6 , 7 . In particular, when supported on TiO 2 , Fe 2 O 3 , etc., gold nanoparticles exhibit high chemoselectivity in reducing a nitro group, whereas other reducing functions are seen in nitroaromatics 8 11 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the gold catalysts can sometimes show hydrogenation activity when gold nanoparticles or atoms are supported on reducible oxides 6 , 7 . In particular, when supported on TiO 2 , Fe 2 O 3 , etc., gold nanoparticles exhibit high chemoselectivity in reducing a nitro group, whereas other reducing functions are seen in nitroaromatics 8 11 .…”
Section: Introductionmentioning
confidence: 99%
“…ZnO nanowires were selected because ZnO has been extensively investigated for use in molecular sensors. Phosphonic acid was used to cap the surface active sites because of their good covering ability on ZnO nanowires. , Methylphosphonic acid (MPA), which is the simplest phosphonic acid, was selected as the model molecule to prove the above-mentioned concepts. MPA has been reported to effectively modulate the catalytic activities of metal oxides (including ZnO) or metal/metal oxide surfaces. Experimental results showed that the MPA modification on a single ZnO nanowire device successfully inhibited aldol condensation on the sensor surface and realized a decrease in the operating temperature for nonanal detection. Interestingly, the sensor response was not deteriorated by MPA modification and accomplished ultralow detection of nonanal, unlike the usual “surface passivation” approaches that often lower sensor sensitivity .…”
Section: Introductionmentioning
confidence: 99%
“…When utilized for oxidation reactions, weakly binding metals such as Au and Ag often depend on metal oxide support materials to aid in O 2 dissociation, limiting the reactive surface to metal sites near the metal/support interface. 62 Hydrogenbonding thiolates or other ligands present an alternative pathway for O 2 dissociation on noninterfacial sites, hypothetically improving overall activity or eliminating the need for reducible support materials. The relationship between surface charge and H-bond strength also suggests that the promotion of O 2 dissociation could be tunable via control of the surface charge.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Additionally, these results suggest that hydrogen-bonding modifiers could be utilized to promote O 2 dissociation and increase the favorability of *O compared to *OO on metal surfaces. When utilized for oxidation reactions, weakly binding metals such as Au and Ag often depend on metal oxide support materials to aid in O 2 dissociation, limiting the reactive surface to metal sites near the metal/support interface . Hydrogen-bonding thiolates or other ligands present an alternative pathway for O 2 dissociation on noninterfacial sites, hypothetically improving overall activity or eliminating the need for reducible support materials.…”
Section: Resultsmentioning
confidence: 99%